Do stock market and banking sectors development promote innovation efficiency? - Low S.-W.; Albada A.; Ghazali N.A.; Nurhatiah Ahmad Chukari (Emerald Group Publishing Ltd., 2024)
Indexed by WOS/SCOPUS/ERA